The Relationship between Body Shaming and Eating Disorder Tendencies in Overweight Early Adult Women - Palullu, Friskia Dewima; Ridfah, Ahmad; Ismail, Ismalandari (Polteknik Ilmu Pemasyarakatan, 2023)
The phenomenon of body shaming behavior is still often found among the public, especially in early adult women. One of the factors that cause individuals to do body shaming is eating disorder behavior that makes individuals less satisfied with body shape and feel that they do not reach ideal standards. This study aims to determine the relationship of body shaming to the tendency of eating disorders in early adult women. The sample in this study was 350 early adult female subjects aged 18-25 years who were domiciled in Makassar City. The sample is obtained by filling out the scan link via google form. Data collection was carried out using two research instruments, namely the body shaming scale and the eating disorder tendency clause. Test the hypothesis using Wilcoxon Theta correlation analysis. The results showed that there was a positive relationship between body shaming and eating disorder tendencies in early adult women with a theta result of 0.536. That is, the higher the tendency to eating disorder, the higher the body shaming experienced by the subject.